Improving the Methodological Basis for Assessing Regulatory Policy in the Agricultural Sector: Areas for Further Research (International Journal of Scientific Research and Management (IJSRM), 2020)
The agricultural sector occupies an important place in post-industrial society. The agricultural sector is associated with such sustainable development goals as economic growth, food security, rational use of resources, increasing the incomes, rural development and preserving the environment. An effective state policy is able to ensure the advancement of the agriculture towards achieving the sustainable development goals. But the formation of state policy should be preceded by a comprehensive assessment of the effectiveness of state measures in previous periods. The article proposes an improving the author’s methodology of comprehensive assessment of the effectiveness of state policy of Ukrainian agriculture. Suggestions for improvement are to strengthen the environmental and social components of assessing the progress of sustainable development goals. The strengthening of the environmental component of the assessment of the progress of sustainable development goals was carried out through the inclusion in the system of assessment of protection indicators and restoration of ecosystems in the process of their use in the agriculture. The strengthening of the social component was achieved through the inclusion in the cost estimation system of the State programs to support housing in rural areas, social investments and own resources of local communities to create a comfortable environment. Approbation of the improved methodology of comprehensive assessment of the effectiveness of state policy in the agriculture was conducted on the example of the agricultural sector of Ukraine in 2010, 2016-2018. The comprehensive assessment showed slow progress in the effectiveness of regulatory policy in agricultural sector of Ukraine in 2010, 2016-2018 and revealed the backlog of social and environmental indicators in the approach to sustainable development goals in comparison with economic ones.